BIAS GENDER DALAM AKSES KREDIT PERBANKAN (Studi pada Pengusaha Mikro dan Menengah di Salatiga) - Linda Ariany Mahastanti; Yeterina Widi Nugrahanti (Modus, 2013)
Women-owned business are often thought to face difculties in applying for and securing bank loans. They face any systematic non-economic discrimination in applying for credit. We test two question related to the success of women owned business in accessing commercial bank fnancing. First, are women-owned business less likely to apply for bank loan than business owned by man?, second if approved on their most recent application, are they more likely to receive a smaller loan?. Using quantitative methodologies with logit and multiple regression analysis, this study explores bias gender in applying bank loan at SMEs in Salatiga. We found gender to be related the size of the loan but not to be to the application for bank loan. These fnding may due to an omitted variable that could capture women’s concerns about maintaining control over their business.Keywords : Women-owned business, small and medium business, bank, credit availability, gender